STRONGLY DEPENDENT CROSSROADS COORDINATION IN THE MAX-PLUS ALGEBRA (Perner's Contacts, 2011)
The paper deals with the coordination of the design of signalized strongly dependent crossroads by using Max-plus algebra. In the first part there is definition of the problem and basic theoretical analysis of Max-plus algebra. In the next section the proposal of signalized crossroads coordination is executed on the basis of Max-plus algebra by using special mathematical software. In the final part there is an evaluation.
Keywords: Coordination; Crossroads; Signalized control; Max-plus algebra